Atraksi Personal Jama’ah Majelis Taklim Dalam Mengikuti Khitobah Ta’tsiriyah - Lestari, Neng Ayu; rojudin, Rojudin; Rustandi, Ridwan (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
The purpose of this study is intended to determine how the motivation, attraction, and relationship of Jama'ah Majelis Taklim Desa pasirwaru through khitobah ta'tsiriyah. The theory used is the theory of interpersonal attraction which explains that a person's liking, positive attitude, and attractiveness to other individuals interact with each other to create compatibility in interpersonal communication. The research method used is descriptive writing through a qualitative approach, and the paradigm used is constructivism. The results show that self-motivation, religious knowledge and friendship encourage participation in khitobah ta'tsiriyah. Applicable material and the communicative role of the ustadz influence the attractiveness of the activity, while social interaction strengthens spirituality and creates a harmonious environment.